A Response of Water Temperature to Wind Speed and Air Temperature in Lake Laut Tawar, Aceh Province, Indonesia - Adhar, Saiful; Mainisa; Andika, Yudho (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Changes in water temperature impact the dynamics of lake ecosystems. Changing climate factors, including wind speed and air temperature, influence the water temperature of lakes. This research aims to analyze the response of water temperature to wind speed and air temperature in Lake Laut Tawar. Observations were conducted from August to September 2023, with a sampling frequency of every two weeks. The results revealed that water temperature, wind speed, and air temperature in Lake Laut Tawar fluctuated according to the presence of light, namely day and night factors. Variations in sunlight intensity lead to hourly fluctuations in air temperatures, while wind speeds vary hourly due to changes in air pressure, consequently resulting in hourly variations in water temperature as well. During daylight hours, air temperature surpasses water temperature, whereas during nighttime hours, water temperature exceeds air temperature. Heat transfer from the air to the water contributes to an increase in water temperature, while the release of heat energy from the surface water into the air leads to a decrease in water temperature. Changes in the water temperature of Lake Laut Tawar are primarily influenced by changes in wind speed and air temperature by 80 percent simultaneously. However, while air temperature showed a partial response, wind speed did not exhibit a significant response. The relationship between these variables can be expressed through a mathematical model Tw = 0.356 Ta + 0.025 W + 15.674, where Tw is water temperature (°C), Ta is air temperature (°C), and W is wind speed (km/minute). Another factor that influences the water temperature of Lake Laut Tawar is the inlet water temperature, which was not observed in this research.